The Croatian Nobility and King Matthias Corvinus -Between Cooperation and Confrontation - Grgin, Borislav (2009)
The rule of Hungarian and Croatian King Matthias Corvinus (1458-1490) had a profound impact upon his kingdom, upon the region, and upon the whole of Europe. Croatia was no exception to this. The paper analyzes the relations between Matthias, the Croatian magnate families, and the lesser and middle nobility. One might conclude that the Croatian nobility gradually started to develop a specific border mentality, coupled with fear, anxiety and insecurity for the future of their homeland. It seems that Croatian society became confronted with multiple challenges that surpassed its ability to cope. Matthias' part of blame was that, as in the rest of the kingdom, he left the country financially exhausted and the magnates dissatisfied with his rule. The fact that Croatia and its nobility were in serious trouble started to be clearly visible immediately after 1490.
Projekt MZOS
ENG